Innovative management model of the organization of methodological work in institutions of higher education - Shalimova, I; Shalimova, A (Problems of Engineer-Pedagogical Education, 2019)
The article is devoted to the problem of managing the organization of methodological work in institutions of higher education basing on innovative principles. The article theoretically substantiates the stages of the development of the organization of methodological work in higher educational institutions; reveals the essence of management of the organization of methodological work in higher medical educational institutions; identifies structural components and main characteristics of this organization; suggests criteria for effective organization of methodological work in higher education institutions: an innovative model of management of methodological work organization in higher education institutions has been developed and partially tested; the article also presents a set of specially created psychological and pedagogical conditions which are expected to increase the effectiveness of methodological work in institutions of higher education together with the implementation of professional multilayer teacher training. The article highlights that the developed innovative model of managing the organization of methodological work in institutions of higher medical education can be practically applied by the heads of methodological services of higher education institutions of various types and forms of ownership.